ASPEK EMOSI DALAM KEHIDUPAN - Syahida Hayati (Universitas Islam Negeri Imam Bonjol Padang, 2015)
Emotion is a reaction or response of individuals to certain conditions, in an effort to resolve the situation dangerous preparations. Emotion is a personal experience, personal, subjective, emotional reactions so that an image of it is different from one individual to another individual, even between one culture with another culture. Emotional disorders may be the first indication searches toward their personality disorder. Fear is a basic emotion, the subjective feeling on terror, causing a strong motivation to do something (to challenge or run), and is a psychological response and complexvigilance. Three components that related teach others namely behavioral, physiological, and cognitive. Emotional process occurs through the basic stages, namely: 1). The emergence of stimulation, 2). Interpretation (assessment) and interpreting cognitive stimulation, 3). Physiological generation, namely an increase in awareness and knowledge of the circumstances surrounding the giving stimulation, and 4). Behavioral manifestations which consists of two forms of expressive response (signal the emotional response) Instrumental response (including interaction with the environment). Almost all kinds of emotional responses, such as anger and fear, increases the activity of the sympathetic nervous system. Basic emotion of fear, anger, sadness, or distress, and enthusiasm can contribute to some psychological disorders. Persistent negative mood or depression, making the memory of the past becomes unpleasant.